Teaching international law - Hilpold, Peter, 1965-; Nesi, Giuseppe (Brill/Nijhoff, 2024)
"This book brings together international lawyers who not only present the state of the art of this discipline but also their own vision and perspective. Traditionally, teachers of international law had considerable influence on the development and the understanding of this subject. The international legal system has profoundly changed, but in time of enormous challenges for the survival of humankind the voice of the teachers should again be heard"--